Influence of the resistance training on heart rate variability, functional capacity and muscle strength in the chronic obstructive pulmonary disease - Ricci-Vitor, A. L. [UNESP] (2013)
Background. The chronic obstructive pulmonary disease (COPD) is associated with the strength and resistance decreasing in addition to the dysfunction on autonomic nervous system (ANS). The aerobic training isolated or in association with the resistance training showed evidence of beneficial effects on an autonomic modulation of COPD; however, there are no studies addressing the effect of isolated resistance training. Aims. This study aims at investigating the influence of resistance training on an autonomic modulation through heart rate variability (HRV), functional capacity and muscle strength in individuals with COPD. Design. Clinical series study. Setting. Outpatients. Population. The study involved 13 individuals with COPD. Methods. The experimental protocol was composed by an initial and final evaluation that consisted in autonomic evaluations (HRV), cardiopulmonary functional capacity evaluation (6-minute walk test) and strength evaluation (dynamometry) in addition by the resistance training performed by 24 sessions lasted 60 minutes each one and on a frequency of three times a week. The intensity was determined initially with 60% of one maximum repetition and was progressively increased in each five sessions until 80%. Results. The HRV temporal and spectral indexes analysis demonstrates improvement of autonomic modulation, with significant statistical increases to sympathetic and parasympathetic components of ANS representing by SDNN, LF and HF. In addition, it was observed significant statistical increases to shoulder abduction and knee flexion strength and functional capacity. Conclusion. The exclusive resistance training performed was able to positively influence the autonomic modulation; in addition it promoted benefits on cardiorespiratory functional capacity and strength benefits in individuals with COPD.Clinical Rehabilitation Impact. This study could contribute to clinical and professionals researchers that act with COPD, even though the resistance component of pulmonary rehabilitation presents consensual benefits on several healthy indicators parameters. There is no evidence about the effects on HRV before. Moreover, this study showed, on clinical practice, the HRV uses as an ANS activity on sinus node evaluation and highlights further importance on scientific context.